Sulfur-resistant anti-scouring metal honeycomb VOCs catalyst and preparation method thereof
By building a multi-material layered structure on a metal honeycomb support, covering active components and combining precious metals and transition metals, the problem of degradation of catalyst performance in a high-erosion environment is solved, and the stability and efficient catalytic performance of the catalyst are improved.
Patent Information
- Application Number
- CN202411892392.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The existing metal honeycomb VOCs catalysts are prone to peel off in high-speed and high-erosion exhaust gas environments, resulting in a degradation of catalyst performance. The firmness and durability of the bonding on the metal support are insufficient, so the purification effect and long service life of the catalyst cannot be continuously guaranteed.
By constructing a multi-material layered structure on a metal support, the active components are coated with alumina and titanium oxide materials to form stable attachment sites, enhancing the stability and catalytic efficiency of the catalyst, and through the stable combination of precious metals and transition metals, displacement and agglomeration are inhibited, and the catalyst's sulfur resistance and long service life are improved.
The stability and efficient catalytic performance of the catalyst in a high-erosion environment are achieved, the service life of the catalyst is extended, and good catalytic performance is maintained in a sulfur-containing atmosphere.
Smart Images

Figure CN119680540A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of metal honeycomb VOCs catalysts and preparation thereof, in particular to a sulfur-resistant and erosion-resistant metal honeycomb VOCs catalyst and a preparation method thereof. Background Art
[0002] Volatile organic compounds (VOCs) are organic compounds with a boiling point below 260°C at normal pressure or a saturated vapor pressure above 70.91 Pa at room temperature. VOCs are emitted into the atmosphere and react with the emissions from fossil fuel combustion (NO X 、SO X ) form sol particles, which in turn cause haze to cause serious damage to the human immune function, and even cause cancer, leukemia, nasopharyngeal cancer or other malignant tumors, bringing great harm to human health.
[0003] The catalytic combustion method can completely burn organic waste gas at a lower ignition temperature with the help of catalysts, oxidize VOCs into CO2 and H2O, and release a large amount of heat to achieve self-heating of the reaction, while recovering heat to achieve maximum energy saving in the whole process. Catalytic combustion has the advantages of wide application range, low ignition temperature, low energy consumption, high efficiency, and no secondary pollution. The core of this technology is an excellent catalyst.
[0004] VOCs catalysts in the prior art are usually used in low-space-velocity and low-scour exhaust gas environments. The catalyst coating is less scourable by exhaust gas and can maintain excellent catalyst performance. However, when used in high-space-velocity and high-scour exhaust gas environments, the catalyst coating will peel off to a certain extent, resulting in a decrease in catalyst performance. Compared with ceramic honeycomb carriers, metal honeycomb carriers have good heat and mass transfer functions and have been widely used, but the adhesion strength and durability of the catalyst coating on the metal carrier are more seriously affected, and the purification effect and long-term service life requirements of the catalyst cannot be continuously and effectively guaranteed. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art metal honeycomb VOCs catalysts in catalytic treatment of volatile organic compounds, such as low catalytic efficiency and poor catalytic stability, and to provide a sulfur-resistant and erosion-resistant metal honeycomb VOCs catalyst and a preparation method thereof. A multi-material layered structure is constructed on a metal carrier through aluminum oxide and titanium oxide materials, so that the active components can obtain more stable attachment sites, thereby achieving the purpose of enhancing the catalytic stability of the catalyst and maintaining the catalytic efficiency.
[0006] The purpose of the present invention is mainly achieved through the following technical solutions:
[0007] A sulfur-resistant and erosion-resistant metal honeycomb VOCs catalyst comprises a metal carrier, on which an aluminum oxide layer and a mixed layer are sequentially coated, wherein the mixed layer is composed of a titanium oxide mixture, an active component and a binder, wherein:
[0008] The metal carrier is a metal honeycomb carrier;
[0009] The mass ratio of the aluminum oxide layer to the total loading mass of the metal carrier is 10.000wt% to 30.000wt%;
[0010] The titanium oxide mixture includes titanium monoxide, titanium dioxide and titanium trioxide, and the titanium monoxide, the titanium dioxide and the titanium trioxide are mixed to form a layered structure; the titanium oxide mixture accounts for 44.800wt% to 80.973wt% of the total loading of the metal carrier;
[0011] The active component is a mixture of reduced noble metal and transition metal oxide, wherein the noble metal accounts for 0.007 wt% to 1.800 wt% of the total loading of the metal carrier, and the transition metal oxide accounts for 3.510 wt% to 17.100 wt% of the total loading.
[0012] The binder accounts for 3.500wt% to 13.500wt% of the total loading of the metal carrier.
[0013] At present, the treatment of volatile organic compounds mainly relies on the catalytic decomposition of volatile organic compounds by catalysts to obtain safer decomposition products. The catalysts used in the prior art are usually ceramic carriers, but the heat and mass transfer functions of ceramic carriers are weak, so the catalytic performance cannot be well exerted. The heat and mass transfer functions of metal carriers are better, but there is a problem of poor adhesion durability of the catalyst coating. Because the metal carrier will oxidize and decay in the natural environment, there will be a large loss, so the catalyst will experience performance degradation when used for a long time.
[0014] The active components of the catalyst in the prior art are brought into contact with volatile organic compounds by coating using the structure of the carrier. The contact area is affected by the structure of the carrier, and the catalyst itself mainly provides catalytic activity. Since the components in the catalyst are relatively simple and cannot constitute its own structure, it cannot have more positive effects on the catalytic performance based on its reliance on the carrier.
[0015] The present invention adopts a metal carrier, and utilizes the heat and mass transfer performance of the metal carrier to effectively improve the catalytic performance. In the titanium oxide mixture, there are three types of substances, namely titanium monoxide, titanium dioxide and titanium trioxide. The structures of these three types of substances are different, so a three-dimensional layered structure will be formed after mixing. The layered structure formed in the titanium oxide mixture can form a three-dimensional structure with a larger contact area on the metal carrier. The active component can be attached to the three-dimensional structure, thereby effectively increasing the contact area between the active component and the reactant, thereby improving the catalyst efficiency. The three-dimensional structure can increase the attachment space of the active component by building a three-dimensional space, and due to the layering, more holes can be constructed, thereby increasing the contact area between the active component and the reactant.
[0016] In the present invention, the combination of the titanium oxide mixture and the active component can inhibit the adsorption of sulfur dioxide and improve the sulfur resistance; the noble metal element and the transition metal oxide are stably combined to inhibit their own displacement and agglomeration, thereby achieving a long service life of the catalyst, thereby effectively avoiding the natural environmental loss that occurs when using a metal carrier, thereby achieving the purpose of both utilizing the advantages of the metal carrier and avoiding the defects of its service life.
[0017] In the present invention, after the metal carrier is pretreated, a thin layer of alumina layer is formed on the inner surface of the carrier. After the alumina layer is poured, the two form a laminated structure. After a certain period of high-temperature calcination, diffusion sintering between the alumina particles is achieved to form a dense alumina laminated structure, which enhances the bonding strength with the carrier, promotes the adsorption and diffusion of reactants in the coating, improves the heat and mass transfer efficiency, and achieves high conversion efficiency of the catalyst. The addition of the binder changes the surface roughness of the alumina layer and enhances the bonding stability with the titanium oxide material. The alumina layer on the inner surface of the pretreated carrier and the added alumina layer are sintered to form a whole, connecting the metal carrier and the titanium oxide mixture, and riveting the three to form a strong bonding coating, reducing the risk of cracking and falling off, and improving the overall anti-scouring ability of the catalyst.
[0018] Furthermore, the aluminum oxide layer includes aluminum oxide and additives, and in the aluminum oxide layer, by mass percentage: the aluminum oxide content is 15.000% to 30.000%, and the additive accounts for 70.000% to 85.000%.
[0019] Furthermore, in the titanium oxide mixture, the titanium monoxide accounts for 0.000wt% to 10.000wt%, the titanium dioxide accounts for 80.000wt% to 100.000wt%, and the titanium trioxide accounts for 0.000wt% to 10.000wt%.
[0020] Furthermore, the noble metal is one of platinum and ruthenium, accounting for 0.007wt% to 1.800wt% of the total loading of the metal carrier;
[0021] The transition metal is one of nickel, molybdenum, cerium, cobalt, zirconium, and tungsten, or a combination of any two of them. When one transition metal is selected, molybdenum or tungsten is preferred, and the oxide accounts for 3.500wt% to 13.500wt% of the total load of the metal carrier; when two transition metals are selected, the total proportion of the two transition metal oxides is 3.510wt% to 17.100wt% of the total load of the metal carrier, wherein one transition metal oxide accounts for 1 to 2 times of the precious metal, and the other transition metal oxide is used as the remaining supplement.
[0022] Furthermore, it also includes a binder, which includes one or a combination of any of silica sol, zirconium sol, aluminum sol, carboxymethyl cellulose, and polyvinyl pyrrolidone, and the binder accounts for 5.000wt% to 15.000wt% of the total loading of the metal carrier.
[0023] A method for preparing a sulfur-resistant and anti-scouring metal honeycomb VOCs catalyst further includes the following steps:
[0024] pretreating the metal support and cleaning the metal support;
[0025] preparing an aluminum oxide layer solution;
[0026] preparing a titanium oxide mixture;
[0027] Prepare an active component precursor solution; then add a titanium oxide mixture and a binder into the solution and mix them evenly to prepare a catalyst slurry;
[0028] pouring the alumina layer solution onto the metal carrier, and after drying, pouring the catalyst slurry onto the metal carrier;
[0029] The metal carrier after pouring is continuously dried and calcined to obtain a metal honeycomb VOCs catalyst.
[0030] At present, in the prior art, the preparation of catalysts mainly adopts the form of directly coating active components on the carrier, which will overly rely on the structural characteristics of the carrier itself and cannot effectively exert the inherent characteristics of the catalyst slurry.
[0031] In the catalyst preparation process of the present invention, the noble metal salt and the transition metal salt are first dissolved and mixed evenly, so that the noble metal and the transition metal can be mixed more evenly, and the dispersion of the active component and the layered structure in the titanium oxide mixture are mixed more evenly, thereby increasing the area to which the active component is attached. Then, adding a reducing agent, an auxiliary agent and a binder to the intermediate mixed liquid can improve the adhesion of the catalyst slurry, so that the active component can be more stably attached to the metal carrier for a long time.
[0032] On this basis, the metal carrier is coated with an alumina layer and a catalyst slurry by pouring, thereby improving the uniformity and stability of the coating. In addition, during the layered pouring process, a more three-dimensional layered structure can be constructed, thereby further increasing the adhesion area of the active components and achieving a stable and efficient catalytic effect.
[0033] Further, the pretreatment of the metal carrier comprises the following steps:
[0034] The metal carrier is placed in a temperature environment of 350° C. to 500° C. for 1 to 3 hours and then cooled to room temperature. The cleaning of the metal carrier comprises the following steps: the metal carrier is purged with 0.2 MPa compressed air.
[0035] Furthermore, the aluminum oxide layer comprises the following steps:
[0036] After mixing alumina powder and additives, heat to 60°C to 90°C and keep warm for 1h to 3h to prepare an alumina layer solution; the additives include one or a combination of carboxymethyl cellulose, polyvinyl alcohol, polyethylene glycol, silica sol, aluminum sol, acetic acid, and nitric acid.
[0037] Furthermore, the preparation of the titanium oxide mixture comprises the following steps:
[0038] Titanium dioxide powder, titanium monoxide powder and titanium trioxide powder are added to an alcohol solvent in proportion, with the alcohol to powder mass ratio being 1:1.0-1.5, the pH value of the mixture is adjusted to 3-6, the mixture is stirred at 50-80°C for 1h-3h, the mixture is dried at 110-130°C for 0.5h-2h, roasted at 350-450°C for 1h-3h, ground and sieved to obtain a titanium oxide mixture; the alcohol solvent comprises one or a combination of ethanol, propanol, ethylene glycol, glycerol, isopropanol and n-butanol;
[0039] When titanium dioxide powder, titanium monoxide powder and titanium trioxide powder are added in proportion, the titanium monoxide accounts for 0.000wt% to 10.000wt%, the titanium dioxide accounts for 80.000wt% to 100.000wt%, and the titanium trioxide accounts for 0.000wt% to 10.000wt%.
[0040] Furthermore, the preparation of the catalyst slurry comprises the following steps:
[0041] Add transition metal salt solution to the noble metal salt solution, dissolve and mix evenly, stir for 0.5h to 3h, and adjust the pH value to 3 to 6;
[0042] Add a reducing agent and an auxiliary agent to carry out a reduction reaction, raise the temperature to 60°C to 90°C, and keep the temperature for 1h to 3h to obtain an active component precursor solution;
[0043] Add the titanium oxide mixture to the active component precursor solution, raise the temperature to 60°C to 90°C, and keep it warm for 1h to 3h;
[0044] The reducing agent includes one or a combination of ethylene glycol, glucose, sodium borohydride, ascorbic acid, ethylenediamine, and ethanolamine, and its content is 3 to 5 times that of the precious metal;
[0045] The auxiliary agent comprises one of hydrochloric acid, nitric acid, acetic acid, oxalic acid and citric acid or any combination thereof, and the content of the auxiliary agent is 2 to 10 times that of the noble metal.
[0046] After the heat preservation is completed, the solution is cooled to room temperature, and a binder is added to prepare a catalyst slurry;
[0047] The binder includes one or more of silica sol, zirconium sol, aluminum sol, carboxymethyl cellulose, and polyvinyl pyrrolidone, and the binder accounts for 3.500wt% to 13.500wt% of the total loading of the metal carrier.
[0048] Furthermore, the pouring coating of the metal carrier comprises the following steps:
[0049] Casting the alumina layer solution and the catalyst slurry in a fluid form sequentially onto the surface of the metal carrier and the surface of its inner pores, and leaving the metal carrier still;
[0050] Repeat pouring, draining and drying the metal carrier, preset the coating mass of the metal carrier, and repeat coating the metal carrier until the alumina layer solution and the catalyst slurry solution reach the preset coating mass of the metal carrier;
[0051] The drying of the metal carrier comprises the following steps: placing the metal carrier in a temperature environment of 110° C. to 130° C., calcining for 0.5 h to 1 h and cooling to room temperature;
[0052] The calcining of the metal carrier comprises the following steps: placing the metal carrier in a temperature environment of 350° C. to 500° C. for 1 to 3 hours and cooling to room temperature.
[0053] In summary, the present invention has the following beneficial effects compared with the prior art:
[0054] In the sulfur-resistant and erosion-resistant metal honeycomb VOCs catalyst of the present invention, a layered structure of a titanium oxide mixture is used to construct a stable active component attachment space, thereby effectively increasing the contact area of the active components while improving the catalyst stability, thereby achieving the purpose of increasing the catalytic efficiency.
[0055] The alumina layer on the inner surface of the pretreated carrier is sintered with the added alumina layer to form a whole, connecting the metal carrier and the titanium oxide mixture, and the three are riveted to form a strong bonding coating, which effectively improves the long-term stability and avoids the problem of reduced catalyst efficiency due to structural damage to the coating. Combined with the stable use of the metal carrier and the increase in the attachment area of the active component, the present invention can obtain excellent catalytic efficiency and long-term catalytic stability.
[0056] In a method for preparing a sulfur-resistant and erosion-resistant metal honeycomb VOCs catalyst, the mixing uniformity of the noble metal ions and the transition metal ions is enhanced by first mixing the noble metal salt solution and the transition metal salt solution, thereby ensuring the stability of the catalyst during use. Secondly, the titanium oxide mixture and the metal mixed salt solution are mixed so that the layered structure of the titanium oxide mixture can more fully accommodate and contact the metal mixed salt solution, thereby achieving the purpose of improving the catalytic efficiency by utilizing the layered structure of the titanium oxide mixture.
[0057] In general, the present invention discloses a metal honeycomb VOCs catalyst that is sulfur-resistant and anti-scouring in the field of metal honeycomb VOCs catalyst and its preparation. The heat and mass transfer performance of the metal carrier is utilized to effectively improve the catalytic performance. The titanium oxide mixture contains three types of substances, namely titanium monoxide, titanium dioxide and titanium trioxide, which form a three-dimensional structure with a larger contact area after mixing, thereby effectively improving the contact area with the reactants. The combination of the titanium oxide mixture and the active component inhibits the adsorption of sulfur dioxide and improves the sulfur resistance. The noble metal element is stably combined with the transition metal oxide to inhibit displacement and agglomeration, thereby avoiding During use, active components are lost, and the alumina layer on the inner surface of the metal carrier cooperates with the cast alumina layer to diffuse and sinter into a dense alumina laminate structure, which enhances the bonding strength with the carrier, improves the heat and mass transfer efficiency, and achieves high conversion efficiency of the catalyst; the addition of binder changes the surface roughness of the alumina layer and enhances the bonding stability with the titanium oxide mixture; based on the treated alumina layer on the inner surface of the carrier, the metal carrier and the titanium oxide mixture are connected through the added alumina layer, and the three are riveted to form a strong bonding coating, which reduces the risk of cracking and falling off and improves the catalyst's ability to resist erosion. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:
[0059] Figure 1 This is a SEM image of the titanium oxide material after mixing of the present invention;
[0060] Figure 2 is the SEM image of the catalyst coating;
[0061] Figure 3 This is a fresh performance diagram of the catalyst of the present invention;
[0062] Figure 4 This is a graph showing the aging performance of the catalyst of the present invention. DETAILED DESCRIPTION
[0063] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0064] Example:
[0065] This embodiment relates to a sulfur-resistant and anti-scouring metal honeycomb VOCs catalyst, including a metal carrier, on which an aluminum oxide layer and a mixed layer are sequentially coated, wherein the mixed layer is composed of a titanium oxide mixture, an active component and a binder, and the metal carrier is a metal honeycomb carrier.
[0066] The aluminum oxide layer accounts for 10.000wt% to 30.000wt% of the total loading of the metal carrier;
[0067] The titanium oxide mixture includes titanium monoxide, titanium dioxide and titanium trioxide, and the titanium monoxide, the titanium dioxide and the titanium trioxide are mixed to form a layered structure; the titanium oxide mixture accounts for 44.800wt% to 80.973wt% of the total loading of the metal carrier;
[0068] The active component is a mixture of reduced noble metal and transition metal oxide, wherein the noble metal accounts for 0.007 wt% to 1.800 wt% of the total loading of the metal carrier, and the transition metal oxide accounts for 3.510 wt% to 17.100 wt% of the total loading.
[0069] The binder accounts for 3.500wt% to 13.500wt% of the total loading of the metal carrier;
[0070] The aluminum oxide layer comprises aluminum oxide and additives, wherein the aluminum oxide accounts for 15.000wt% to 30.000wt% of the aluminum oxide layer by weight, and the additives account for 70.000% to 85.000% of the aluminum oxide layer by weight.
[0071] In the titanium oxide mixture, the titanium monoxide accounts for 0.000wt% to 10.000wt%, the titanium dioxide accounts for 80.000wt% to 100.000wt%, and the titanium trioxide accounts for 0.000wt% to 10.000wt%.
[0072] The noble metal is one of platinum and ruthenium, accounting for 0.007wt% to 1.800wt% of the total loading of the metal carrier;
[0073] The transition metal is one of nickel, molybdenum, cerium, cobalt, zirconium, and tungsten, or a combination of any two of them. When one transition metal is selected, molybdenum or tungsten is preferred, and the oxide accounts for 3.500wt% to 13.500wt% of the total load of the metal carrier; when two transition metals are selected, the total proportion of the two transition metal oxides is 3.510wt% to 17.100% of the total load of the metal carrier, wherein one transition metal oxide accounts for 1 to 2 times that of the noble metal, and the other transition metal oxide is used as the remaining supplement.
[0074] It also includes a binder, which includes one or a combination of any two or more substances including silica sol, zirconium sol, aluminum sol, carboxymethyl cellulose, and polyvinyl pyrrolidone. The mass proportion of the binder is 3.500wt% to 13.500wt% of the total loading of the metal carrier.
[0075] In the preferred embodiment of this embodiment, Figure 1 to Figure 4 As shown, the metal carrier is made of iron-chromium-aluminum, including a shell and a foil strip, and the honeycomb mesh number is 100-900 mesh. The cylindrical dimensions are: radius: 50mm-550mm, height: 50mm-200mm, and the square dimensions are: length: 100mm-1000mm, width: 100mm-1000mm, and height: 50mm-300mm.
[0076] This ensures that the present embodiment can achieve the catalytic effect by utilizing it, and can also improve the stability of the metal carrier and the contact area of the active components of the metal carrier.
[0077] This embodiment also relates to a method for preparing a sulfur-resistant and anti-scouring metal honeycomb VOCs catalyst, comprising the following steps:
[0078] pretreating the metal support and cleaning the metal support;
[0079] preparing an aluminum oxide layer solution;
[0080] Preparing a noble metal salt solution and a transition metal salt solution, adding and mixing the noble metal salt and the transition metal salt in a designed mass ratio to dissolve them, and preparing an active component precursor solution;
[0081] Adding a titanium oxide mixture into the active component precursor solution and mixing them evenly to form an intermediate mixed solution, and then adding a reducing agent, an auxiliary agent and a binder to the intermediate mixed solution to prepare a catalyst slurry;
[0082] pouring the alumina layer solution onto the metal carrier, and after drying, pouring the catalyst slurry onto the metal carrier;
[0083] The metal carrier after pouring is continuously dried and calcined to obtain a metal honeycomb VOCs catalyst.
[0084] In this embodiment, the heat and mass transfer performance of the metal carrier is utilized to effectively improve the catalytic performance; there are three types of substances in the titanium oxide mixture, namely titanium monoxide, titanium dioxide and titanium trioxide, and the structures of these three types of substances are different. After mixing, a three-dimensional structure with a larger contact area is formed on the metal carrier, and the active components are attached thereto, which effectively increases the contact area with the reactants and improves the catalyst efficiency; the adsorption of sulfur dioxide is inhibited by the combination of the titanium oxide mixture and the active components, thereby improving the sulfur resistance; the noble metal element is stably combined with the transition metal oxide to inhibit displacement and agglomeration, avoid the loss of active components during use, and achieve a long service life of the catalyst; the metal carrier After pretreatment, a thin layer of alumina layer is formed on the inner surface of the body, which is combined with the cast alumina layer. After a certain period of high-temperature calcination, the diffusion sintering between the alumina particles is achieved to form a dense alumina laminated structure, which enhances the bonding strength with the carrier, improves the heat and mass transfer efficiency, and achieves high conversion efficiency of the catalyst; the addition of the binder changes the surface roughness of the alumina layer and enhances the bonding stability with the titanium oxide mixture; based on the alumina layer on the inner surface of the treated carrier, the metal carrier and the titanium oxide mixture are connected through the added alumina layer, and the three are riveted to form a strong bonding coating, which reduces the risk of cracking and falling off and improves the catalyst's ability to resist erosion.
[0085] The final results show that after the coating is subjected to high temperature impact of 650°C and purged for a long time (10 minutes) at a gas pressure of 0.7MPa, the coating does not crack and the shedding rate is ≤1%; and it has good catalyst freshness and aging performance under a certain sulfur-containing atmosphere.
[0086] Furthermore, the preparation of the catalyst slurry comprises the following steps:
[0087] The noble metal salt and the transition metal salt are dissolved and mixed evenly, stirred for 0.5h to 1h, and the pH value is adjusted to 3 to 6;
[0088] Add a reducing agent and an auxiliary agent to carry out a reduction reaction, raise the temperature to 60°C to 90°C, and keep the temperature for 1h to 3h to obtain an active component precursor solution;
[0089] At this time, the mixed solution of the noble metal salt, the transition metal salt, the reducing agent and the auxiliary agent is heated to 60° C. and kept warm for 1 to 3 hours to obtain an effective catalytic active component concentration.
[0090] If the temperature is raised to 75°C and kept warm for 1 to 3 hours, the concentration of the active component can reach its peak value.
[0091] If the temperature is raised to 90°C and kept for 1 to 3 hours, other chemical reactions will occur and the concentration of active components will tend to decrease.
[0092] The main influencing factor here is temperature. The effect can be achieved within the range of 1h to 3h. If the time is less than 1h, the temperature transfer is not uniform, and if the time exceeds 3h, there is a risk of additional chemical reactions.
[0093] Add the titanium oxide mixture to the active component solution, raise the temperature to 60℃~90℃, and keep it warm for 1h~3h.
[0094] At this time, the mixed solution of the titanium oxide mixture, active component solution, and binder is heated to 60° C. and kept warm for 1 to 3 hours. The titanium oxide mixture can be dispersed in the active component solution without producing additional reactions, thereby ensuring the stability of the components of the titanium oxide mixture.
[0095] If the temperature is raised to 75°C and kept warm for 1 to 3 hours, the titanium oxide mixture can be dispersed in the active component solution without causing additional chemical reactions, thus ensuring the stability of the composition of the titanium oxide mixture.
[0096] If the temperature is raised to 90°C and kept warm for 1 to 3 hours, the titanium oxide mixture can be dispersed in the active component solution without causing any additional chemical reactions, thus ensuring the stability of the composition of the titanium oxide mixture.
[0097] The main influencing factor here is temperature. Within the temperature range, the diffusion rate of the titanium oxide mixture is accelerated and the stability is guaranteed, so that the effect can be achieved within the range of 1h to 3h. If the time is less than 1h, the temperature transfer is not uniform enough, and if the time exceeds 3h, there is a risk of additional chemical reactions.
[0098] After the heat preservation is completed, the solution is cooled to room temperature, and a binder is added to prepare a catalyst slurry;
[0099] The reducing agent includes one or a combination of any two or more of ethylene glycol, glucose, sodium borohydride, ascorbic acid, ethylenediamine, and ethanolamine.
[0100] The auxiliary agent includes one of hydrochloric acid, nitric acid, acetic acid, oxalic acid and citric acid or a combination of any two or more substances.
[0101] Furthermore, the preparation of the titanium oxide mixture includes the following steps: adding titanium dioxide powder, titanium monoxide powder, and titanium trioxide powder to an alcohol solvent in proportion, with the alcohol to powder mass ratio being 1:1.0 to 1.5, adjusting the pH value of the mixture to 3 to 6, stirring the mixture at a temperature of 50°C to 80°C for 1h to 3h, drying the mixture at 110°C to 130°C for 0.5h to 2h, roasting at 350°C to 450°C for 1h to 3h, grinding, and sieving to obtain a titanium oxide mixture;
[0102] The alcohol solvent includes one or a combination of any two or more of ethanol, propanol, ethylene glycol, glycerol, isopropanol, and n-butanol;
[0103] The preparation of the aluminum oxide layer solution includes the following steps: mixing the aluminum oxide powder and the additive, heating to 60° C. to 90° C., and keeping the temperature for 1 h to 3 h to prepare the aluminum oxide layer solution;
[0104] At this time, the mixed solution of alumina powder and additives is heated to 60°C and kept warm for 1 to 3 hours. The alumina powder is evenly diffused in the additive and no additional chemical reaction occurs, thereby ensuring the stability of the composition of the alumina layer solution.
[0105] If the temperature is raised to 75°C and kept warm for 1 to 3 hours, the alumina powder will be evenly diffused in the additive and no additional chemical reaction will occur, thus ensuring the stability of the composition of the alumina layer solution.
[0106] If the temperature is raised to 90°C and kept for 1 to 3 hours, the alumina powder will be evenly diffused in the additive and no additional chemical reaction will occur, thus ensuring the stability of the composition of the alumina layer solution.
[0107] The main influencing factor here is temperature. Within the temperature range, the diffusion rate of aluminum oxide is accelerated and the stability is guaranteed, so that the effect can be achieved within the range of 1h to 3h. If the time is less than 1h, the temperature transfer is not uniform, resulting in uneven diffusion of aluminum oxide. If the time exceeds 3h, there is a risk of additional chemical reactions.
[0108] The additives include one or a combination of any two or more of carboxymethyl cellulose, polyvinyl alcohol, polyethylene glycol, silica sol, aluminum sol, acetic acid and nitric acid.
[0109] Furthermore, the pretreatment of the metal carrier comprises the following steps: the pretreatment of the metal carrier comprises the following steps: placing the metal carrier in a temperature environment of 350°C to 500°C, calcining it for 1h to 3h and cooling it to room temperature.
[0110] The cleaning of the metal carrier comprises the following steps: blowing the metal carrier with 0.2 MPa compressed air.
[0111] The pouring coating of the metal carrier comprises the following steps: pouring the alumina layer solution and the catalyst slurry in a fluid form onto the surface of the metal carrier and the surface of its inner pores in sequence, and leaving the metal carrier still; repeatedly coating the metal carrier until the alumina layer solution and the catalyst slurry solution reach the preset coating quality of the metal carrier;
[0112] The drying of the metal carrier comprises the following steps: placing the metal carrier in a temperature environment of 110° C. to 130° C., calcining for 0.5 h to 1 h and cooling to room temperature;
[0113] The calcining of the metal carrier comprises the following steps: placing the metal carrier in a temperature environment of 350° C. to 500° C. for 1 to 3 hours and cooling to room temperature.
[0114] In this embodiment, when the alumina layer solution and the catalyst slurry are coated, the alumina layer solution needs to be coated first and then the catalyst slurry, thereby relying on the direct contact between the alumina layer and the metal carrier to improve the stability of the metal carrier, and being able to utilize the combination of the alumina layer and the metal carrier to provide a more three-dimensional carrying space for the catalyst slurry.
[0115] In this embodiment, the following specific implementation methods may be adopted:
[0116] According to the preferred scheme of a sulfur-resistant and anti-scouring metal honeycomb VOCs catalyst of this embodiment, the component ratio is carried out as basic example 1:
[0117] Pretreatment carrier: optional The metal honeycomb carrier, the outer shell foil strip is made of iron-chromium-aluminum, pre-treated at 500℃ for 1h, and cooled to room temperature;
[0118] Preparation of aluminum oxide layer solution: mixing aluminum oxide powder, polyvinyl alcohol solution, polyethylene glycol solution, nitric acid solution and silica sol in a mass ratio of 30:6:1:118:9, heating to 80° C. and keeping the temperature for 1 hour to prepare an aluminum oxide layer solution;
[0119] Preparation of titanium oxide mixture: adding titanium monoxide, titanium dioxide and titanium trioxide powders in a mass ratio of 5:90:5 to ethylene glycol, with a mass ratio of powder to ethylene glycol of 1.2:1, adjusting pH to 6.0, stirring at 60°C for 1 hour, drying at 120°C for 1 hour, calcining at 400°C for 1 hour, grinding and sieving to obtain a titanium oxide mixture;
[0120] Preparation of active component precursor solution: according to the total loading amount of the metal carrier, the material is calculated, platinum salt is added according to 1.154% of the total loading amount of the metal carrier, zirconium salt is added according to 2.308% of the total loading amount of the metal carrier, and tungsten salt is added according to 6.713% of the total loading amount of the metal carrier, and the mixture is dissolved and mixed evenly, stirred for 0.5h, and the pH is adjusted to 4.0; ascorbic acid is added, and its added mass is 3 times that of platinum, and then oxalic acid is added, and its added mass is 10 times that of platinum; after stirring evenly, the solution is heated to 80°C, and stirred and kept warm for 1h; the active component precursor solution is prepared;
[0121] Preparation of catalyst slurry: Add the prepared titanium oxide mixture, the added mass of which is 60.414% of the total metal carrier loading, keep stirring and keep warm for 1 hour; after the insulation is completed, cool the mixed solution to room temperature, and then add silica sol, the added mass (converted into silicon dioxide) is 7.843% of the total metal carrier loading, keep stirring for 0.5 hour, and prepare catalyst slurry.
[0122] Preparation of catalyst: Use pouring method to evenly distribute the alumina layer solution along the direction of the carrier honeycomb channel, drain the excess alumina layer solution after standing for 30 seconds, dry the carrier at 110℃ for 0.5h and weigh it to ensure that the residual alumina layer mass after drying is 0.542g; Use pouring method again to evenly distribute the catalyst slurry along the direction of the carrier honeycomb channel, drain the excess catalyst slurry after standing for 30s, and dry it at 110℃ for 0.5h; then calcine the poured catalyst at 500℃ for 1h to ensure that after removing the alumina layer mass, the residual dry basis mass is 1.973g. Marked as basic example 1.
[0123] The comparative example is designed according to the basic example 1. The basic example 1 and comparative examples 1 to 17 in this embodiment are all specific embodiments that need to be protected by the present invention:
[0124] Comparative Example 1: In this comparative example, the preparation process of the catalyst is the same as that of Basic Example 1, except that the mass ratio of titanium monoxide, titanium dioxide, and titanium trioxide is 0:9:1. This is marked as Comparative Example 1.
[0125] Comparative Example 2: In this comparative example, the preparation process of the catalyst is the same as that of Basic Example 1, except that the mass ratio of titanium monoxide, titanium dioxide, and titanium trioxide is 1:9:0. This is marked as Comparative Example 2.
[0126] Comparative Example 3: In this comparative example, the preparation process of the catalyst is the same as that of Basic Example 1, except that the mass ratio of titanium monoxide, titanium dioxide, and titanium trioxide is 1:8:1. This is marked as Comparative Example 3.
[0127] Comparative Example 4: In this comparative example, the preparation process of the catalyst is the same as that of Basic Example 1, except that the mass ratio of titanium monoxide, titanium dioxide, and titanium trioxide is 0:10:0. This is marked as Comparative Example 4.
[0128] In Basic Example 1 and Comparative Examples 1 to 4, the types of transition metals and binders are the same, and the proportions of titanium monoxide, titanium dioxide, and titanium trioxide in the titanium oxide mixture are different. The purpose is to compare the differences in fresh performance and aged performance of catalysts with different proportions of the titanium oxide mixture.
[0129] Comparative Example 5: In this comparative example, the preparation process of the catalyst is the same as that of Basic Example 1, except that no tungsten salt or zirconium salt is added, and only platinum salt is selected, the proportion remains unchanged, and only the type is changed. This is marked as Comparative Example 5.
[0130] Comparative Example 6: In this comparative example, the preparation process of the catalyst is the same as that of Basic Example 1, except that no zirconium salt is added, and only platinum salt and tungsten salt are selected, the proportion remains unchanged, and only the type is changed. This is marked as Comparative Example 6.
[0131] Comparative Example 7: In this comparative example, the preparation process of the catalyst is the same as that of Basic Example 1, and the only difference is that the zirconium salt is replaced by nickel salt, the proportion remains unchanged, and only the type is changed. It is marked as Comparative Example 7.
[0132] Comparative Example 8: In this comparative example, the preparation process of the catalyst is the same as that of Basic Example 1, and the only difference is that tungsten salt and zirconium salt are substituted for nickel salt and cerium salt, and the proportion remains unchanged, only the type is changed. It is marked as Comparative Example 8.
[0133] Basic Example 1 and Comparative Examples 5 to 8 have the same ratio of titanium monoxide, titanium dioxide and titanium trioxide in the titanium oxide mixture, but different types of transition metals with the same proportions. The purpose is to compare the differences in fresh performance and aged performance of catalysts with different transition metal types.
[0134] Comparative Example 9: In this comparative example, the preparation process of the catalyst is the same as that of Basic Example 1, and the only difference is that the silica sol is replaced by zirconium sol with the same molar ratio.
[0135] Comparative Example 10: In this comparative example, the preparation process of the catalyst is the same as that of Basic Example 1, and the only difference is that the silica sol is replaced by an aluminum sol with the same molar ratio.
[0136] Comparative Example 11: In this comparative example, the preparation process of the catalyst is the same as that of Basic Example 1, except that the silica sol is removed and no binder is added. This is marked as Comparative Example 11.
[0137] Comparative Example 12: In this comparative example, the preparation process of the catalyst is the same as that of Basic Example 1, and the only difference is that the silica sol is replaced with polyvinylpyrrolidone of the same molar ratio.
[0138] Comparative Example 13: In this comparative example, the preparation process of the catalyst is the same as that of Basic Example 1, the only difference being that the silica sol is replaced with carboxymethyl cellulose in the same molar ratio and is marked as Comparative Example 13.
[0139] Comparative Example 14: In this comparative example, the preparation process of the catalyst is the same as that of Basic Example 1, with the only difference being that the silica sol is replaced with a 1:1 mass ratio mixture of silicon and zirconium sol with the same molar ratio, marked as Comparative Example 14.
[0140] Comparative Example 15: In this comparative example, the preparation process of the catalyst is the same as that of Basic Example 1, with the only difference being that the silica sol is replaced with a 1:1 mass ratio mixture of zirconium and aluminum sols with the same molar ratio, marked as Comparative Example 15.
[0141] Comparative Example 16: In this comparative example, the preparation process of the catalyst is the same as that of Basic Example 1, with the only difference being that the silica sol is replaced with a 1:1 mixture of aluminum sol and polyvinylpyrrolidone in the same molar ratio, marked as Comparative Example 16.
[0142] Comparative Example 17: In this comparative example, the preparation process of the catalyst is the same as that of Basic Example 1, with the only difference being that the silica sol is replaced by a 1:1:1 mixture of aluminum sol, polyvinylpyrrolidone and carboxymethyl cellulose in the same molar ratio, marked as Comparative Example 17.
[0143] The difference between Basic Example 1 and Comparative Examples 9 to 17 is that different types of binders are selected, and the purpose is to study the effects of different binders on the catalyst shedding rate.
[0144] By comparing the freshness performance and aging performance test results of basic example 1 and comparative examples 1 to 4, as shown in FIG. Figure 3 , Figure 4 As shown, the results show that:
[0145] The fresh performance of the basic example is improved by 5%-15% compared with the control example, and the aging performance is improved by 10%-30% compared with the control example, thanks to the layered structure formed by the titanium oxide mixture mixed in proportion, such as Figure 1 As shown, more attachment sites are provided for the active components, the attachment amount of the active components increases, the contact area with the reactants is increased, and the freshness of the catalyst is improved; as the proportion of titanium monoxide and titanium trioxide materials increases, the surface attachment sites are overlapped and covered, the attachment amount decreases, and the catalyst performance is affected and reduced; the single titanium dioxide mixture cannot form a layered structure, the spatial structure is not effectively utilized, the attachment sites are reduced, the attachment amount is reduced, and the catalyst performance is affected and reduced; after long-term use, the layered structure effectively curbs the collapse of the titanium oxide mixture, avoids overlapping coverage between active components, and maintains the catalyst performance.
[0146] By comparing the freshness performance and aging performance test results of basic example 1 and comparative examples 5 to 8, as shown in FIG. Figure 3 , Figure 4 As shown, the results show that:
[0147] The platinum, tungsten and zirconium composite oxides formed after calcination effectively inhibit the displacement and agglomeration of platinum, and maintain the high dispersion, stable particle size and electronic state of platinum; the appropriate ratio of platinum, tungsten and zirconium can give full play to the performance of the oxides, enhance the interaction between active components, improve its own stability, and achieve a long service life of the catalyst; the composite oxide and titanium oxide mixture work together to ensure the acidity of the catalyst, inhibit the adsorption of sulfur dioxide by the catalyst, and improve the sulfur resistance, so that the catalyst can still maintain good fresh aging performance in a sulfur-containing atmosphere.
[0148] The coating shedding rate was tested for Basic Example 1 and Comparative Examples 9 to 17. The coating in this example is the total loading amount of the metal carrier.
[0149] The coating shedding rate test method is as follows:
[0150] Before the test, the catalyst needs to be kept at 120℃ for 1h and weighed as M1 in g; after cooling to room temperature for 1h and degreasing and dehydrating compressed air (0.7±0.05)MPa compressed air, with a pipe diameter of 0.008m, the purge distance from the catalyst end face is ≤3cm, and the end face is purged evenly and slowly back and forth for at least 3 cycles to observe whether there is dust falling off or flying on the catalyst; the catalyst is again kept at 120℃ for 1h and weighed as M2 in g; the calculated value of the catalyst coating mass (catalyst volume × loading amount) is recorded as M0 in grams (g).
[0151] After the catalyst is tested for coating shedding, the percentage of the coating weight of the catalyst coating shedding to the total coating weight of the catalyst coating is calculated as follows:
[0152]
[0153] Where:
[0154] μ——coating shedding rate, %;
[0155] M1——The mass of the sample before testing, in grams (g);
[0156] M2——The mass of the sample after testing, in grams (g);
[0157] M0 – the mass of the coating in the catalyst, in grams (g).
[0158] By comparing the shedding rate test results of basic example 1 and comparative examples 9 to 17, as shown in Table 1, combined with the attached Figure 2The results show that after adding silica sol as a binder, the surface roughness of the alumina layer is changed, and the bonding stability with the titanium oxide mixture is enhanced; based on the treated alumina layer on the inner surface of the carrier, the metal carrier and the titanium oxide mixture are connected by the added alumina layer, and the three are riveted to form a strong bonding coating, which reduces the risk of cracking and shedding, and improves the catalyst's anti-scouring ability. The composition achieved that after the catalyst was subjected to a high temperature of 650℃ and purged at 0.7MPa pressure for 10min, the coating shedding rate was ≤1%.
[0159] Table 1: Catalyst shedding rate test
[0160] Theoretical coating mass g Before purge g After purging g Drop rate% Basic Example 1 1.54 1.54 1.53 0.65% Comparative Example 9 1.54 1.54 1.32 14.52% Comparative Example 10 1.54 1.54 1.38 10.63% Comparative Example 11 1.54 1.54 0.63 59.04% Comparative Example 12 1.54 1.54 1.12 27.41% Comparative Example 13 1.54 1.54 1.42 7.91% Comparative Example 14 1.54 1.55 1.49 3.89% Comparative Example 15 1.54 1.54 1.41 8.36% Comparative Example 16 1.54 1.54 1.32 14.45% Comparative Example 17 1.54 1.54 1.05 31.89%
[0161] The catalyst performance test method is as follows:
[0162] The concentration of sulfur-containing exhaust gas before and after passing through the catalyst is detected by a chromatograph to determine the ignition temperature and conversion efficiency temperature; the catalyst is aged in the atmosphere and tested in the same sulfur-containing atmosphere to determine the ignition temperature and conversion efficiency after aging. The test boundaries are as follows:
[0163] Table 2: Catalyst aging test boundaries
[0164] Test atmosphere <![CDATA[50 ppm sulfur dioxide + 100 ppm propane, O2: 5%, H2O: 20%, balance gas: N2.]]> Aging conditions <![CDATA[650℃@20h, 10% H2O, 50ppm sulfur dioxide, 1Wh -1 > Test airspeed <![CDATA[2.5W h -1 ]]> Test temperature 120℃、250℃、300℃、350℃、400℃、450℃ Test Status Steady State
[0165] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A sulfur-resistant and anti-scouring metal honeycomb VOCs catalyst, characterized in that: The invention comprises a metal carrier, wherein the metal carrier is coated with an aluminum oxide layer and a mixed layer in sequence, wherein the mixed layer is composed of a titanium oxide mixture, an active component and a binder, wherein The metal carrier is a metal honeycomb carrier; The aluminum oxide layer accounts for 10.000wt% to 30.000wt% of the total loading of the metal carrier; The titanium oxide mixture includes titanium monoxide, titanium dioxide and titanium trioxide, and the titanium monoxide, the titanium dioxide and the titanium trioxide are mixed to form a layered structure; the titanium oxide mixture accounts for 44.800wt% to 80.973wt% of the total loading of the metal carrier; The active component is a mixture of reduced noble metal and transition metal oxide, wherein the noble metal accounts for 0.007wt% to 1.800wt% of the total load of the metal carrier, and the transition metal oxide accounts for 3.510wt% to 17.100wt% of the total load; The binder accounts for 3.500wt% to 13.500wt% of the total loading of the metal carrier.
2. The sulfur-resistant and anti-erosion metal honeycomb VOCs catalyst according to claim 1, characterized in that: The material of the aluminum oxide layer includes aluminum oxide and additives, wherein the aluminum oxide accounts for 15.000wt% to 30.000wt% of the aluminum oxide layer by weight, and the additives account for 70.000% to 85.000% of the aluminum oxide layer by weight.
3. The sulfur-resistant and anti-erosion metal honeycomb VOCs catalyst according to claim 1, characterized in that: In the titanium oxide mixture, the titanium monoxide accounts for 0.000wt% to 10.000wt%, the titanium dioxide accounts for 80.000wt% to 100.000wt%, and the titanium trioxide accounts for 0.000wt% to 10.000wt%.
4. The sulfur-resistant and anti-erosion metal honeycomb VOCs catalyst according to claim 1, characterized in that: The noble metal is one of platinum and ruthenium, accounting for 0.007wt% to 1.800wt% of the total loading of the metal carrier; The transition metal is one of nickel, molybdenum, cerium, cobalt, zirconium and tungsten, or a combination of any two thereof.
5. The sulfur-resistant and anti-erosion metal honeycomb VOCs catalyst according to claim 1, characterized in that: The binder includes one or a combination of any two or more of silica sol, zirconium sol, aluminum sol, carboxymethyl cellulose, and polyvinyl pyrrolidone.
6. A method for preparing a sulfur-resistant and anti-scouring metal honeycomb VOCs catalyst, characterized in that: The following steps are involved: pretreating the metal support and cleaning the metal support; preparing an aluminum oxide layer solution; preparing a titanium oxide mixture; Prepare an active component precursor solution; then add a titanium oxide mixture and a binder into the solution and mix them evenly to prepare a catalyst slurry; pouring the alumina layer solution onto the metal carrier, and after drying, pouring the catalyst slurry onto the metal carrier; The metal carrier after pouring is continuously dried and calcined to obtain a metal honeycomb VOCs catalyst.
7. The method for preparing a sulfur-resistant and anti-erosion metal honeycomb VOCs catalyst according to claim 6, characterized in that: The pretreatment of the metal carrier comprises the following steps: placing the metal carrier in a temperature environment of 350° C. to 500° C. for 1 h to 3 h and cooling to room temperature; The cleaning of the metal carrier comprises the following steps: blowing the metal carrier with 0.2 MPa compressed air.
8. The method for preparing a sulfur-resistant and anti-erosion metal honeycomb VOCs catalyst according to claim 6, characterized in that: The aluminum oxide layer solution preparation comprises the following steps: After mixing the alumina powder and the additive, heat to 60°C to 90°C and keep warm for 1h to 3h to prepare an alumina layer solution; The additives include one or a combination of any two or more of carboxymethyl cellulose, polyvinyl alcohol, polyethylene glycol, silica sol, aluminum sol, acetic acid and nitric acid.
9. The method for preparing a sulfur-resistant and anti-erosion metal honeycomb VOCs catalyst according to claim 6, characterized in that: The titanium oxide mixture preparation comprises the following steps: Add titanium dioxide powder, titanium monoxide powder and titanium trioxide powder to an alcohol solvent in a ratio of 0 to 1 part by weight of titanium dioxide powder, 8 to 10 parts by weight of titanium monoxide powder and 0 to 1 part by weight of titanium trioxide powder, wherein the alcohol to powder mass ratio is 1:1.0 to 1.5, adjust the pH value of the mixture to 3 to 6, stir the mixture at a temperature of 50 to 80° C. for 1 h to 3 h, dry the mixture at 110 to 130° C. for 0.5 h to 2 h, roast it at 350 to 450° C. for 1 h to 3 h, grind it, and sieve it to obtain a titanium oxide mixture; The alcohol solvent includes one of ethanol, propanol, ethylene glycol, glycerol, isopropanol, and n-butanol, or a combination of any two or more of the above substances.
10. The method for preparing a sulfur-resistant and anti-erosion metal honeycomb VOCs catalyst according to claim 6, characterized in that: The preparation of the catalyst slurry comprises the following steps: The noble metal salt and the transition metal salt are dissolved and mixed evenly, stirred for 0.5h to 1h, and the pH value is adjusted to 3 to 6; Add a reducing agent and an auxiliary agent to carry out a reduction reaction, raise the temperature to 60°C to 90°C, and keep the temperature for 1h to 3h to obtain an active component precursor solution; Add the titanium oxide mixture to the active component precursor solution, raise the temperature to 60°C to 90°C, and keep it warm for 1h to 3h; The reducing agent includes one or a combination of any two or more of ethylene glycol, glucose, sodium borohydride, ascorbic acid, ethylenediamine, and ethanolamine, and its content is 3 to 5 times that of the precious metal; The auxiliary agent includes one or a combination of hydrochloric acid, nitric acid, acetic acid, oxalic acid, and citric acid, and its content is 2 to 10 times that of the precious metal; After the heat preservation is completed, the mixture is cooled to room temperature, and then a binder is added and stirred for 0.5 h to 1 h to prepare a catalyst slurry; The binder includes one or a combination of any two or more of silica sol, zirconium sol, aluminum sol, carboxymethyl cellulose, and polyvinyl pyrrolidone.
11. The method for preparing a sulfur-resistant and anti-erosion metal honeycomb VOCs catalyst according to claim 6, characterized in that: The pouring coating of the metal carrier comprises the following steps: Casting the alumina layer solution and the catalyst slurry in a fluid form sequentially onto the surface of the metal carrier and the surface of its inner pores, and leaving the metal carrier still; Repeat the coating of the metal carrier until the alumina layer solution and the catalyst slurry solution reach the coating mass of the preset metal carrier; The continuous drying of the metal carrier is drying, and the drying comprises the following steps: placing the metal carrier in a temperature environment of 110° C. to 130° C. for calcining for 0.5 h to 1 h and cooling to room temperature; The calcining of the metal carrier comprises the following steps: placing the metal carrier in a temperature environment of 350° C. to 500° C. for 1 to 3 hours and cooling to room temperature.
Citation Information
Patent Citations
Titanium oxide and alumina alkali metal compositions
CN101060928A
C / TiO mesoporous composite photocatalyst and preparation method thereof
CN105536762A
Composite catalyst, activated composite catalyst, preparation method and application thereof
CN109701557A
Metal sheet having photocatalytic activity, and its manufacturing method
JP2002047558A
Catalyst for purifying exhaust gases and method for manufacturing same
US4350613A